Patient profile and treatment outcome in a tuberculosis unit in Kolkata, West Bengal - Sardar, Jadab Chandra; Karmakar, Prasanta Ray; Biswas, Subrata (International Journal Of Community Medicine And Public Health, 2020)
Background: Tuberculosis is caused by bacteria (Mycobacterium tuberculosis) that most often affect the lungs. Tuberculosis is curable and preventable. It is estimated that 1/3rd of current global population is infected asymptomatically with tuberculosis, of which 5-10% will develop clinical disease during life time. Methods: This descriptive observational study was conducted in Tuberculosis Unit, Bagbazar, Kolkata. Initially demographic data and initial clinical data were collected. Then follow up data were collected until the end of treatment. Data were compiled and analysed. Frequency and percentages were calculated. Results: Male patients were more (69.12%). Majority (61.76%) of the patients were in the age group of 19-50 years of age, followed by 50-60 years (17.64%). Common presenting complaints were cough (61.76%), fever (63.24%), loss of appetite (54.41%), respiratory distress (11.76%), haemoptysis (10.29%), loss of weight (10.29%), swelling of gland (5.88%). Success rate (treatment completed and cured) was about 90%. Conclusions: Tuberculosis was found more in male and in active age group. Treatment of tuberculosis had a very high success rate.